2004
DOI: 10.1002/ptr.1452
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal constituents of Clytostoma ramentaceum and Mansoa hirsuta

Abstract: Ethanol extracts of Clytostoma ramentaceum Bur. & K. Schum and Mansoa hirsuta DC. (Bignoniaceae) inhibited the growth of standardized cultures of Aspergillus niger and Fusarium oxysporum, at concentrations of 400 microg and 500 microg, in bioautographic assays. The activity-guided fractionation of C. ramentaceum extract afforded ursolic acid and 2-(3',4'-dihydroxyphenyl) ethanol, both active against the test fungi (100 microg). These compounds are reported for the first time in C. ramentaceum and were not dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
1
32
0
5
Order By: Relevance
“…Silva, unpublished data). In traditional medicine, the leaves of this species have been used to control diabetes (Chaves andReinhard 2003, Agra et al 2008) while the ethanol extract has inhibited the growth of Aspergillus niger and Fusarium oxysporum cultures (Rocha et al 2004). The antioxidant activity of M. hirsuta was also demonstrated by Braga et al (2000) while isolated proanthocyanidins were capable of inhibiting angiotensin-converting enzyme (ACE) (Campana et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Silva, unpublished data). In traditional medicine, the leaves of this species have been used to control diabetes (Chaves andReinhard 2003, Agra et al 2008) while the ethanol extract has inhibited the growth of Aspergillus niger and Fusarium oxysporum cultures (Rocha et al 2004). The antioxidant activity of M. hirsuta was also demonstrated by Braga et al (2000) while isolated proanthocyanidins were capable of inhibiting angiotensin-converting enzyme (ACE) (Campana et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The MIC of the H. ovalifolia extract against T. rubrum strains was 0.25 mg/mL and the E. uniflora extract exhibited antifungal activity against 19 of the 30 isolates at a concentration of 0.5 mg/mL. Rocha et al (2004) demonstrated antifungal activity of Clytostoma ramentaceum and Mansoa hirsuta (Bignoniaceae) when testing the low and medium polar fractions at concentrations of 0.1 to 0.3 mg/mL. Pacciaroni et al (2008) isolated several flavonoids from the aerial parts of Heterothalamus alienus and tested these compounds against clinical isolates of dermatophytes.…”
Section: Resultsmentioning
confidence: 91%
“…& K. Schum and Mansoa hirsute DC. inhibited the growth of the fungi Aspergillus niger and Fusarium oxysporum (Rocha et al, 2004); a mixture of ellagitannins isolated from Punica granatum L. and two naphthoquinones isolated from Tabebuia avellanedae Lorenz ex Grisebach demonstrated antibacterial activity against multiresistant Staphylococcus aureus strains (Machado et al, 2003); the alcoholic extracts of the pods and flowers of Tecoma sambucifolia H.B.K. displayed cytotoxicity against a human hepatoma cell line (Alguacil et al, 2000); the biological screening of some fractions derived from the leaves and liana of Macfadyena unguiscati (L.) revealed antitumoral and antitrypanosomal activities (Duarte et al, 2000); and an aqueous ethanol extract of Jacaranda caucana Pittier showed in vivo antitumoral and in vitro cytotoxic activity against the P-388 lymphocytic leukemia system (Ogura et al, 1977).…”
Section: Resultsmentioning
confidence: 99%